Prevention of STI Transmission among Men Who Have Sex with Men in Indonesia through Circumcision Behavior - Mona Safitri Fatiah; Rispah Purba (Jurnal Bidan Cerdas, 2023)
Introduction: The proportion of Sexually Transmitted Infections (STIs) among MSM has increased by around 0,2% from the first quarter and second quarter of 2023, for this reason, prevention efforts are needed in the form of implementing circumcision behavior among men. Objective: to understand the relationship between circumcision and transmission of STIs through MSM in Indonesia. Method: This research has a cross-sectional design with the population being men who have sex with men (MSM) across 24 provinces in Indonesia totaling 6,000 people, while the research sample is mostly MSM totaling 4,290 people with inclusion criteria being: men who are at least 15 years old, have ever had sex with men at least once in the past year, and have lived in the survey city for around one month. Samples were taken using the Respondent Driven Sampling (RDS) technique. The data used is secondary data in the form of 2018-2019 Biological Behavior Survey (STBP) data. Data in the study were analyzed using logistic regression analysis of risk factor models using STATA 14 software. Results: MSM who were circumcised had a 3.0 times greater chance of not having STI symptoms compared to MSM who were not circumcised (95% CI: 2.5- 3.7) after controlling for sex-buying and selling behavior. Conclusion: circumcision behavior is one of the efforts to prevent the spread of STI among MSM, recommending the need to create regulations regarding the importance of circumcision behavior in Indonesia.